Incidence, Characteristics, and Implications of Seizures in Patients With Glioblastoma. (August 2017) - Shin, John Y.; Kizilbash, Sani H.; Robinson, Steven; Uhm, Joon H.; Jatoi, Aminah
Background: Seizures in patients with glioblastoma are associated with worse quality of life. However, their incidence, clinical characteristics, and prognostic implications are less well characterized. Objective: This study was undertaken to provide a contemporary experience along with benchmark data relevant to the above in patients with glioblastoma. It also sought to reexplore improved survival with seizures, as observed by others. Methods: In this single-institution study, patients with glioblastoma from 2010 through 2014 had their medical records reviewed in detail. Results: Among 122 patients, 58 (48%) had a seizure history. Of these, 67% had more than 1, 41% had generalized seizures, and most received antiseizure medication (most commonly levetiracetam). The median survival for patients with seizures was 1.66 years and 0.87 years for those without (hazard ratio for risk of death with seizures: 0.72; 95% confidence interval: 0.43, 1.21; P = .22 by the log-rank test). Conclusion: Seizures are common in patients with glioblastoma and, in contrast to earlier reports, are not associated with a statistically significant improvement in survival.